The Impact of Herbicide-Resistant Rice Technology on Phenotypic Diversity and Population Structure of United States Weedy Rice . Issue 3 (13th August 2014) - Burgos, Nilda Roma; Singh, Vijay; Tseng, Te Ming; Black, Howard; Young, Nelson D.; Huang, Zhongyun; Hyma, Katie E.; Gealy, David R.; Caicedo, Ana L.
Abstract : Use of herbicide-resistant rice cultivars in the United States has led to the emergence of herbicide-resistant weedy rice formed predominantly by hybridization of cultivars with historical weeds characterized by black hulls and awns . Abstract: The use of herbicide-resistant (HR ) Clearfield rice ( Oryza sativa ) to control weedy rice has increased in the past 12 years to constitute about 60% of rice acreage in Arkansas, where most U.S. rice is grown. To assess the impact of HR cultivated rice on the herbicide resistance and population structure of weedy rice, weedy samples were collected from commercial fields with a history of Clearfield rice. Panicles from each weedy type were harvested and tested for resistance to imazethapyr. The majority of plants sampled had at least 20% resistant offspring. These resistant weeds were 97 to 199 cm tall and initiated flowering from 78 to 128 d, generally later than recorded for accessions collected prior to the widespread use of Clearfield rice (i.e. historical accessions). Whereas the majority (70%) of historical accessions had straw-colored hulls, only 30% of contemporary HR weedy rice had straw-colored hulls. Analysis of genotyping-by-sequencing data showed that HR weeds were not genetically structured according to hull color, whereas historical weedy rice was separated into straw-hull and black-hull populations. A significant portion of the local rice crop genome was introgressed into HR weedy rice, which was rare in historical weedy accessions. Admixture analyses showed that HR weeds tend to possess crop haplotypes in the portion of chromosome 2 containing the ACETOLACTATE SYNTHASE gene, which confers herbicide resistance to Clearfield rice. Thus, U.S. HR weedy rice is a distinct population relative to historical weedy rice and shows modifications in morphology and phenology that are relevant to weed management.